Gram-scale production of graphene oxide-TiO2 nanorod composites : towards high-activity photocatalytic materials - Liu, Jincheng (2012)
Here we present a simple two-phase assembling method to produce high-quality graphene oxide-TiO2 nanorod composites (GO-TiO2 NRCs) on gram scale. TiO2 nanorods dispersed in toluene are synthesized from a facile two-phase hydrothermal method. The effective attachment of TiO2 nanorods on the whole GO sheets at the water-toluene interface is confirmed by Transmission Electron Microscope (TEM), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS). The as-synthesized TiO2 nanorods show a slightly higher efficiency in the photocatalytic degradation of C. I. Acid Orange 7 (AO7) irradiated under UV light (λ=254 nm) and higher antibacterial activity under simulated sunlight than that of TiO2 nanoparticles with the same diameter. After combined with graphene oxide (GO), the GO-TiO2 NRCs show much higher photocatalytic activities than that of TiO2 nanorods alone and the GO-TiO2 nanoparticle composites (GO-TiO2 NPCs). The ratio of TiO2 and GO has no evident effect on the photocatalytic activity of GO-TiO2 NRCs when all the TiO2 nanorods are anchored on the GO sheets. The higher photocatalytic activity of GO-TiO2 NRCs is ascribed to the anti-charge recombination and the more (101) facets. Considering the superior photocatalytic activity of GO-TiO2 NRCs and the fact that they can been easily mass-produced, we expect this material may find important applications in environmental engineering and other fields.